Efek Minyak Esensial Lavender Dibandingkan dengan Minyak Esensial Jahe terhadap Intensitas Nyeri Menstruasi pada Remaja - Wasis Pujiati; Mae Sri Hartati W; Elsi Dwi Hapsari (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Menstrual pain is the pain in the abdomen which is perceived before or during menstruation, that even when the menstrual pain is heavily painful, the sufferers leave their activities. Research in 2011 showed that the rate of occurrence of primary menstrual pain in Indonesian adolescences was about 54.89%. Various therapies have been used to cure the pain, both pharmacologically and nonpharmacologically. Pharmacologically, it is done by the usage of NSAID, and non-pharmacologically is done by using essential oil.Objective: To know about the effects of lavender essential oil compared to ginger essential oil toward the intensity of menstrual pain in the adolescences of SHS 1 Muncar.Method: True experimental design, with randomized pretest posttest design plan. Time of data retrieval was August-September 2014 in SMA 1 Muncar, Banyuwangi, East Java. Population in this research were female adolescences in class of X and XI, with the amount of 260 students, with samples’ amount of 30 for each treatment group. The sampling technique was simple random sampling. The dependent variable are the giving of lavender and ginger essential oils, meanwhile the independent variable are the reduction of the intensity of menstrual pain. Instrument which was used was Numerical Rating Scale. The data analysis used the Wilcoxon and Mann-Whitney Test.Result and Discussion: The intensity of pain before and after intervention of essential oil of lavender and ginger are 5,47±1,19 vs 2,93±1,53, P=0,00 and 5,40±0,96 vs 2,93±1,43, P=0,00, respectively. Comparison of the effects essential oil of lavender and ginger have P >0,05.Conclusion: Both lavender essential oil and ginger essential oil are effective in reducing the intensity of menstrual pain in adolescences. Keywords: Menstrual pain, Essential oils, Lavender, Ginger, Adolescences